ESTRATEGIAS Y MODELOS DE FINANCIACIÓN DEL DOCUMENTAL INTERACTIVO Y TRANSMEDIA - Arnau Gifreu-Castells,Valentina Moreno, (Fonseca, Journal of Communication, 2023)
The digital revolution has facilitated the expansion of new audiovisual formats, bringing with them new possibilities for the public. The interactive documentary, a genre in gestation that is continually growing, has benefited from these new logics, models and dynamics. The novelty lies in the possibility of the spectator interacting with the story.